Development and validation of the HPV-WAK questionnaire for assessing women’s awareness and knowledge in Iran - Parisa Ebrahimi; Fatemeh Pourmotahari; Hamed Rahimi (PLoS ONE, 2026)
Background Evidence indicates that knowledge about Human Papillomavirus remains limited in Iran. This study aimed to develop and psychometrically validate the Human Papillomavirus-related women’s awareness and knowledge (HPV-WAK) questionnaire for Iranian women. Methods A mixed-methods study was conducted. First, an item pool was created through a rapid scoping review. Subsequently, the questionnaire’s psychometric properties were assessed, including face validity, content validity (CVR/CVI), and hypothesis testing for construct validity (known groups comparison). Reliability was evaluated via internal consistency (KR-20) and inter-rater reliability (kappa). A cut-off score was determined using ROC analysis. Results From an initial 551 items, 122 were selected for the item pool. Following translation and cultural adaptation, a 50-item version underwent face validity assessment, leading to revisions of 5 items. The final 29-item questionnaire showed strong content validity (S-CVI/Ave = 0.97; S-CVI/UA = 0.83) after eliminating 21 items with low CVR (<0.62). construct validity was confirmed via known groups comparison (P < 0.001). The questionnaire demonstrated moderate internal consistency (KR-20 = 0.757) and excellent inter-rater reliability (Kappa = 0.854). The optimal cut-off score was 26. Conclusions The HPV-WAK is a valid and reliable questionnaire with strong psychometric properties, making it suitable for use by public health professionals to assess HPV knowledge, identify gaps, and evaluate interventions among Iranian women of childbearing age.